Photosynthetic responses of understory savanna plants: Implications for plant persistence in savannas under tree encroachment - Rossatto, Davi Rodrigo [UNESP]; de Araújo, Paola Eduarda [UNESP]; da Silva, Bianca Helena Porfírio [UNESP]; Franco, Augusto César (Elsevier, 2018)
Savannas are ecosystems where plants are expected to have leaf-level adaptations conferring tolerance to high irradiances, which characterizes this type of open canopy vegetation. The neotropical savannas of Brazil (Cerrado) harbour a large diversity of heliophilous herbaceous species, which are threatened by the current invasion of those open canopy habitats by forest trees, increasing tree density and canopy cover, thereby strongly reducing light availability. In this study, we measured leaf pigment concentrations, specific leaf area and light response curves of photosynthesis to determine whether herbaceous species of open savanna habitats were less tolerant to shade than the ones that were more characteristic of forested savanna. Relative to species of forested savannas, herbaceous species of open savannas had heavier leaves with higher concentration of carotenoids. They also achieved higher photosynthetic rates, reaching light compensation and saturation at higher irradiances. Based on measurements of light compensation points and of prevailing irradiances in forested savannas, leaves of most herbaceous species of more open savannas would be strongly light-limited in sites with a dense woody layer. In summary, we provide evidence that forest tree encroachment of savannas would select for leaf trait combinations in the understory vegetation that would favor shade tolerance and, depending on the degree of leaf acclimatization to shade of individual species, could strongly constrain persistence of the current understory vegetation.
Keywords: Cerrado; Encroachment; Leaf functional traits; Leaf gas exchange; Leaf pigments; Shade tolerance